The Association of Knowledge, Health Worker Roles, and Husband’s Support with Antenatal Care Attendance Among Pregnant Women at the Community Health Center - Elfina; Siti Nurcahyani Ritonga; Sumarah; Ranti Lestari; Mahfuzhah Deswita Puteri (CV. Get Press Indonesia, 2025)
Antenatal Care (ANC) visits are essential for monitoring maternal and fetal health and detecting pregnancy complications early. However, ANC completion rates are influenced by various factors. This study examines the associations between maternal knowledge, husband's support, and healthcare worker roles with ANC visit completion at Kayu Laut Community Health Center, Mandailing Natal Regency. Using a cross-sectional descriptive correlational design, 67 pregnant women were recruited through accidental sampling. Data were collected via validated questionnaires and analyzed using Chi-square tests. Results showed significant associations between ANC completion and maternal knowledge, husband's support, and healthcare worker roles. Women with adequate knowledge, strong spousal support, and positive perceptions of healthcare workers demonstrated higher ANC completion rates.The findings emphasize the importance of educational interventions, family involvement, and improved healthcare service quality to enhance ANC adherence. Collaborative efforts among healthcare workers, husbands, and pregnant women are critical for optimizing maternal and neonatal health outcomes.